PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG DAMPAK PERNIKAHAN DINI DI SMKN 1 KOTA PROBOLINGGO - Cahyaningtyas, Beta Permata; Indriarti, Ina; Keswara, Nila Widya (NHM PRESS, 2024)
Teenagers are individuals aged between 10 and 24 years and are not married. During adolescence, significant physical and psychological changes occur. In today's teenagers, early marriage often occurs. Indonesia is ranked second after Cambodia in cases of early marriage. According to Basic Health Research, 2.6% of women were married before the age of 15 years, and 23.9% were married between the ages of 15-19 years (RISKESDAS, 2018). Increasing the level of education and empowering women is also the key to reducing cases of early marriage. This research aims to determine the effect of reproductive health education on young women's knowledge about the impact of early marriage at SMKN 1 Probolinggo city in 2023. The type of research used is correlational analysis with a cross sectional design. The population in this study were all young female students in class XI of SMKN 1 Probolinggo City with a sample of 203 female students obtained using random sampling techniques. Data were collected using a questionnaire and research data were analyzed using the Wilcoxon test. The results of the research, before being given health education, the majority of respondents had good knowledge (1.5%), enough (21.7%) and respondents who had less knowledge (76.8%). Meanwhile, after being given health education, the majority had good knowledge (96.1%), enough (3.9%) and respondents with less knowledge (0%). From the results of the Wilxcon test, the p-value = 0.000 < 0.05 means that there is an influence of reproductive health education on the knowledge of young women about the impact of early marriage at SMKN 1 Probolinggo City in 2023. So reproductive health education needs to be promoted today. by related parties to minimize cases of early marriage and maternal mortality rates.